Assessment of tempromandibular joint space and condylar position in patients with myofacial pain dysfunction syndromes by using cone beam computed tomography - Mahmood, Hassan Ali; Kurshid, Katayon Nathm; Ali, Sarkawt Hamad; Ali, Sangar Hamid (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objectives: Joint space assessment and condylar relation in the glenoid fossa is considered as integral component of the clinical assessment of the patient with tempromandibular joint disorder. Any variant from normal tempromandibular joint may affect the diagnosis and management of the case. Methods: Thirty patients with unilateral myofacial pain dysfunction syndrome were included in this study (14 male and 16 female). Joint space analysis was performed by cone beam computed tomography for all patients. Analysis of data for joint spaces (anterior, middle, posterior, medial and lateral) was performed by using t-test. Results: The joint spaces and condyle positions in anterior, superior and posterior regions showed less joint space and statistically significant difference (P <0.05) from same joint space of normal side. No statistically significant differences were found in space value between middle and lateral condylar space of the diseased side and normal side of the patient. The joint spaces in normal sides were between 2 to 3.2 mm. Age and gender variations showed no statistical differences. Conclusion: The use of cone beam computed tomography for examination of tempromandibular joint space in patients with myofacial pain dysfunction syndrome give a good diagnostic criteria for affected side.